Epidemiology of birth defects in a national hospital-based birth defect surveillance spot in Southern Jiangsu, China, 2014–2018 - Zhou, Ying; Yang, Di; Mao, Xueqin; Zhou, Hua; Wang, Li (Frontiers in Medicine, 2023)
Objective As the only hospital-based national surveillance spot of birth defects (BDs) in Changzhou city located in the economically developed eastern part of China, Changzhou Maternal and Child Health Care Hospital has encountered serious challenges in BD prevention. This study aimed to describe the epidemiology of total BDs born in the hospital from 2014 to 2018. Methods The data were collected from the national hospital-based birth defect surveillance system. BD prevalence was calculated by Poisson distribution. Trends of prevalence and the associations regarding information with BDs were analyzed by Poisson regression. Results The reported prevalence of total BDs was 313.92 (95% confidence interval [CI]: 299.59–328.76) per 10,000 perinatal infants (PIs), while the perinatal prevalence of BD was 160.19 (95% CI: 150.00–170.89) per 10,000 PIs. A remarkable uptrend in the prevalence of BDs was noticed with a prevalence rate ratio (PRR) of 1.09 (95% CI: 1.04–1.14) and 1.13 (95% CI: 1.09–1.16), respectively. Congenital heart disease (CHD), cleft lip with or without cleft palate (CL/P), congenital malformation of the kidney (CMK), polydactyly, Down syndrome (DS), cystic hygroma, neural tube defect (NTD), and congenital talipes equinovarus (CTE) were common types of total BDs. Mothers living in the urban area (PRR = 1.67, 95% CI:1.50–1.87), male fetuses (PRR = 1.16, 95% CI: 1.05–1.28), and maternal age younger than 20 (PRR = 2.28, 95% CI: 1.60–3.25) and 25 years (PRR = 1.41, 95% CI: 1.22–1.63) or older than 35 years (PRR = 1.18, 95% CI: 1.00–1.40) were risk factors for BD occurrence. Conclusion The reported prevalence of total BDs was nearly two times higher than the perinatal prevalence of BDs in PIs, and the ranks of total BDs and BDs in PIs were different. Mothers living in the urban area, male fetuses, and maternal ages younger than 25 or older than 35 years were risk factors for BD incidence. Thus, improving prenatal examination technology, expanding the surveillance time quantum of BDs, and keeping maternal health may be warranted.